Nursing perspectives supportive care of the oncology patient (Houston : Medivision, 1997)
This program explores the challenges of managing pain in the oncology patient, examining the pain initiative and its impact on oncology care in the United State. It describes principles of pain management, explains that fatigue is a side effect of cancer treatment, and considers nutritional oncology as an approach to cost and complication prevention
97-1104N, NTSC-VHS
Keywords: Medical, Oncology -- nursing; Nursing Care